The mutH gene regulates the replication and methylation of the pMB1 origin. - Russell, D W (1991)
DNA methylation is known to regulate several prokaryotic replication origins. In particular, the Escherichia coli chromosomal origin oriC and the pMB1 plasmid origin (which is homologous to the ColE1 origin) replicate poorly when hemimethylated at dam (GATC) sites. Because the mismatch repair protein MutH is known to recognize hemimethylated dam sites, its role in the replication of these origins was investigated. The results presented here show that the mutH gene product is partially responsible for the poor replication of the pMB1 origin when hemimethylated but has no effect on the replication of oriC. Methylation levels at individual dam sites suggest that the MutH protein binds to an inverted repeat in the pMB1 replication primer promoter. These findings suggest a mechanism for the coordinated control of DNA repair and replication.